ANALISIS PERPUTARAN PIUTANG USAHA, PERPUTARAN HUTANG USAHA DAN PERPUTARAN PERSEDIAAN TERHADAP MODAL KERJA - Sarbullah, Sarbullah; Marhamah, Marhamah; Nindita, Yoga; Rizkiyani, Putri Nisma (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2025)
Working capital represents the total current assets used to finance the company's daily operational activities. Lack of managerial attention to working capital management can lead to various issues such as uncollectible receivables, delays in supplier payments, and excessive inventory accumulation. This study aims to analyze the effect of receivables turnover, payables turnover, and inventory turnover on working capital at CV Sumber Jaya Makmur Purbalingga. The method used is descriptive quantitative, employing multiple linear regression analysis, classical assumption tests, t-tests, F-tests, and the coefficient of determination using SPSS version 23. The data analyzed consists of financial reports over a 72-month period from January 2017 to December 2022. The results indicate that only receivables turnover has a significant effect on working capital (Sig. 0.000 < 0.05), while payables turnover and inventory turnover do not show a significant impact. The model demonstrates an estimation strength of 55.4%. These findings highlight the importance of receivables management in maintaining stable working capital. Future researchers are encouraged to consider additional variables such as liquidity ratios as alternative predictors of working capital.